The Strategic Role of the C-130 Hercules Aircraft as A Component of Indonesia's Air Defense in Facing National Security Threats - Mulyana, Pandhu Adhitya; Setiawan, Asep; Hasanudin, Usni (International Journal of Social Service and Research, 2026)
Indonesia's air defense faces increasing complexity from military and non-military threats, such as smuggling, transnational terrorism, and airspace violations, driven by its strategic geographic location. This research aims to analyze the operational readiness of the C-130 Hercules aircraft and its strategic role in Indonesia's air defense. Drawing on a theoretical framework encompassing Defense Theory, Air Power Theory, and Triple Helix Theory, this qualitative study employs literature reviews and in-depth interviews with sources from the National Air Defense Operations Command and Depohar 10. The results indicate that the C-130 Hercules plays a crucial role in Indonesia's air defense, although its operational readiness remains suboptimal due to technical, logistical, and managerial challenges. Factors such as aging aircraft, structural fatigue, and delays in importing spare parts contribute to these readiness issues. However, the Triple Helix ecosystem— involving the government (policy and procurement), industry (PT Dirgantara Indonesia for maintenance and spare parts), and academia (research on modern maintenance and human resource development)—plays a key role in strengthening its strategic capacity. The Indonesian Air Force's tiered maintenance system, revitalization, and modernization programs reflect ongoing efforts to sustain the Hercules as a vital strategic asset for Indonesia's defense mobility.